Platelet function analyser (PFA‐100) results and von Willebrand factor deficiency: a 16‐year 'real‐world' experience. (10th March 2015) - Ardillon, L.; Ternisien, C.; Fouassier, M.; Sigaud, M.; Lefrançois, A.; Pacault, M.; Ribeyrol, O.; Fressinaud, E.; Boisseau, P.; Trossaërt, M.
Summary The platelet function analyser (PFA‐100) is a biological tool designed to explore primary haemostasis. This system has thus been widely demonstrated as reliable in detecting von Willebrand factor (VWF) deficiency. However, most studies were based on patients benefitting from regular medical care and accurate diagnosis, and it would seem probable that the results were somewhat optimistic, and do not reflect its performances in 'real‐world' situations. We have chosen to study the reliability of PFA‐100 for screening VWF ristocetin cofactor (VWF:RCo) deficiency. We retrospectively analysed the results (n = 6431) of 4027 patients referred to our centre between October 1997 and June 2013 and in whom PFA‐Epi, PFA‐ADP, and VWF:RCo activity had been evaluated. We studied the influence of blood group on the results and the performances of each method in a subgroup of 213 patients with genetically confirmed von Willebrand disease. We have shown that the PFA‐100 system, in our experience, constitutes an excellent screening test for detecting VWF:RCo deficiency, whatever the clinical situation, in 'real‐world' conditions. The negative predictive value (NPV), the positive predictive value, the sensitivity and the specificity were respectively: 0.98, 0.51, 0.98 and 0.40. When values adjusted for blood group are used, NPV and sensitivity are inferior to those using normal values which have not been adjusted for blood group. We have shown the PFA‐100 method to be more efficient in screening for VWF deficiency than the VWF:RCo technique.